Endurance exercise with reduced muscle glycogen content influences substrate utilization and attenuates acute mTORC1- and autophagic signaling in human type I and type II muscle fibers - Horwath, O; Cornet, L; Strömlind, H; Moberg, M; Edman, S; Söderlund, K; Checa, A; Ruas, J L; Blomstrand, E (bioRxiv, 2024)
Exercising with low muscle glycogen content can improve training adaptation, but the mechanisms underlying the muscular adaptation are still largely unknown. In this study, we measured substrate utilization and cell signaling in different muscle fiber types during exercise and investigated a possible link between these variables. Five subjects performed a single leg cycling exercise in the evening (day 1) with the purpose of reducing glycogen stores. The following morning (day 2), they performed two-legged cycling at ∼70% of VO2peak for 1h. Muscle biopsies were taken from both legs pre- and post-exercise for enzymatic analyses of glycogen, metabolite concentrations using LC-MS/MS-based quantification, and protein signaling using Western blot in pools of type I or type II fibers. Glycogen content was 60-65% lower for both fiber types (P<0.01) in the leg that exercised on day 1 (low leg) compared to the other leg with normal level of glycogen (normal leg) before the cycling exercise on day 2. Glycogen utilization during exercise was significantly less in both fiber types in the low compared to the normal leg (P<0.05). In the low leg, there was a 14- and 6-fold increase in long-chain fatty acids conjugated to carnitine in type I and type II fibers, respectively, post-exercise. This increase was 3-4 times larger than in the normal leg (P<0.05). Post-exercise, mTORSer2448 phosphorylation was increased in both fiber types in the normal leg (P<0.05) but remained unchanged in both fiber types in the low leg together with an increase in eEF2Thr56 phosphorylation in type I fibers (P<0.01). Exercise induced a reduction in the autophagy marker LC3B-II in both fiber types and legs, but the post-exercise level was higher in both fiber types in the low leg (P<0.05). Accordingly, the LC3B-II/I ratio decreased only in the normal leg (75% for type I and 87% for type II, P<0.01). Starting an endurance exercise session with low glycogen availability leads to profound changes in substrate utilization in both type I and type II fibers. This may reduce the mTORC1 signaling response, primarily in type I muscle fibers, and attenuate the normally observed reduction in autophagy.